(Mis)diagnosing silence a cultural criticism of the Virginia Tech news coverage of silence as public pedagogy - Hao, Richie Neil (Ann Arbor Michigan ProQuest LLC, 2009)
On April 16, 2007, Virginia Tech became the site of the deadliest school shooting in U.S. history. As the mainstream media talked about the possible causes, they ultimately pointed out that perpetrator Seung-Hui Cho's silence should have been detected as a warning sign to his violent rampage. Due to the U.S. media's construction of silence through Cho, I argue that the news coverage helped perpetuate the notion that silence is not only a negative attribute in education, but it is also a dangerous behavior that can pose a threat to people's safety. Therefore, this dissertation asks, how did the news coverage of Virginia Tech serve as a public pedagogy of silence? Silence is introduced as a pedagogical performance by using critical communication pedagogy as a theoretical framework to deconstruct problematic media constructions of silence.--Abstract.
Thesis (Ph.D.)--Southern Illinois University Carbondale, 2009.
Keywords: Criticism and interpretation